Pengaruh Penerapan E-Filling, Tingkat Pemahaman Perpajakan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus pada KPP Pratama Cakung) - Stella Oktaviani; Florencia Irena Lawita (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
E-Filling Implementation, Tax is one of the largest state revenues. To achieve the target of state revenue from taxation, the Director General of Taxes takes steps in the context of sustainable tax reform, including tax reform in the policy sector and reform in tax administration. So that tax reform creates a healthy and competitive taxation system in encouraging taxpayers to fulfill their rights and tax obligations. This study discusses the effect of moral obligation, taxpayer environment, religiosity and tax modernization on individual taxpayer compliance behavior at KPP Pratama Cakung. The sampling technique used is Accidental Sampling and data obtained as many as 100 respondents from individual taxpayer compliance atKPP Pratama Cakung. Data analysis techniques and Hypothesis testing to test each variable was carried out by descriptive statistical tests, validity tests, reliability tests, classical assumption tests, multiple regression analysis tests, F tests and t tests using the SPSS 25 program. Based on the tests that have been carried out, it can be concluded that E-Filling Implementation, Taxpayer Understanding and Taxpayer Awareness Affect Taxpayer Compliance at KPP Pratama Cakung.